Modulators of platelet function in aging - Krishna S. Iyer; Sanjana Dayal (Platelets, 2020)
Platelets are small, anucleated effector cells that play an important role in linking the hemostatic and inflammatory processes in the body. Platelet function is known to be altered under various inflammatory conditions including aging. A gain in platelet function during aging can increase the risk of thrombotic events, such as stroke and acute myocardial infarction. Anti-platelet therapy is designed to reduce risk of serious cerebrovascular and cardiovascular events, but the adverse consequences of therapy, such as risk for bleeding increases with aging as well. Age-associated comorbidities such as obesity, diabetes, and hyperlipidemia also contribute to increased platelet activity and thus can enhance the risk of thrombosis. Therefore, identification of unique mechanisms of platelet dysfunction in aging and in age-associated comorbidities is warranted to design novel antiplatelet drugs. This review outlines some of the current areas of research on aging-related mechanisms of platelet hyperactivity and addresses the clinical urgency for designing anti-platelet therapies toward novel molecular targets in the aging population.